Synthesis and characterization of Tb2O3/TiO2 nanoparticles and their application in dye sensitized solar cells - Singh, Rajwant (My University, 2013)
Surface coating of TiO2 nanoparticles with Tb2O3 has been carried out using sol-gel and hydrothermal method. X-ray diffraction (XRD) analysis reveals the formation of anatase phase TiO2 nanoparticles. Energy dispersive x-ray spectroscopy (EDAX) shows the presence of Tb2O3 on the surface of TiO2 nanoparticles. Transmission electron microscopy (TEM) confirms the coating of Tb2O3 on the TiO2 nanoparticles surface. The strong quenching in photoluminescence emission, in case of Tb2O3/TiO2 nanoparticles as compared to TiO2 nanoparticles, has been attributed to the decrease in recombination rate of photo-generated electron–hole pairs. The synthesized nanoparticles have been employed as a photo-anode in DSSCs. From the dye desorption study, it has been revealed that ccompared to TiO2 electrodes, Tb2O3/TiO2 electrodes adsorbed more dye. The photoelectrochemical property of the Tb2O3/TiO2 based DSSC has been found to improve as compared to bare TiO2 based DSSC, and the energy conversion efficiency increases from 1.54% to 1.88% under the illumination of simulated light of 100 mW/cm2. Tb2O3 coating played a significant role in minimizing electron-hole recombination which occurred at TiO2 surface by trapping electrons and facilitating them to anode.
MT, SPMS